The Democratization Process in the Western Balkans in the Last 20 Years: Interethnic Relations and Security Implications - Katerina Veljanoska; Oliver Andonov; Goran Shibakovski (Romanian Journal of European Affairs)
The process of democratization in Western Balkans is connected with the process of state-building before and after the reconstruction. After the break-up of Yugoslavia, the region became a brutal battleground as different nation-based groups fought to define the boundaries of a set of new states in the Balkans. One of the key challenges related to the democratization of the Western Balkan countries is resolving the issues with their neighbours. However, political pragmatism and bilateral relations between the countries of the Balkans, including their internal conflicts do not exclude informal alliances, but as a temporary form of exploitation of the current political and security situation or in order to achieve their own national interests. One of the key tools in the achievement of national interests, especially expressed in the Balkan countries is represented by the ethnic minorities. Ethnic minorities in the Balkans cannot be overlooked and most of them are seen as a destabilizing factor in the countries in which minorities live. Without overcoming prejudices and differences of the past, the Western Balkans could not continue their independent development. Democratization of the Western Balkans means that improving the peace and coexistence should not be viewed in the past, but in the current process of cooperation. The EU integration process of Western Balkan countries and the democratization process of the region will have to be implemented in the future if the political elites in Western Balkan countries wish to achieve security, stability and prosperity of their societies.